Cover Image. Issue 6 (19th December 2020) - Unknown
Abstract : Ternary biodegradable polymer blends of poly (lactic acid) (PLA), poly (butylene succinate) (PBS), and poly (ε‐caprolactone) (PCL) with the composition 45/10/45 wt% exhibit partial‐wetting morphology, where the minor phase is present as self‐assembled droplets at the co‐continuous interface of the other two major phases. In the article e10145, the crystallization of the components in the various blends was thoroughly investigated by Dario Cavallo and colleagues. The image displays the crystallization of PBS co‐continuous phase, which nucleates at the surface of previously crystallized PLA spherulites. PBS forms a transcrystalline layer whose growth engulfs the molten PCL partial‐wetting droplets. (doi.org/10.1002/pcr2.10145 ) Abstract : Ternary biodegradable polymer blends of poly (lactic acid) (PLA), poly (butylene succinate) (PBS), and poly (ε‐caprolactone) (PCL) with the composition 45/10/45 wt% exhibit partial‐wetting morphology, where the minor phase is present as self‐assembled droplets at the co‐continuous interface of the other two major phases. In the article e10145, the crystallization of the components in the various blends was thoroughly investigated by Dario Cavallo and colleagues. The image displays the crystallization of PBS co‐continuous phase, which nucleates at the surface of previously crystallized PLA spherulites. PBS forms a transcrystalline layer whose growth engulfs the molten PCL partial‐wetting droplets. (doi.org/10.1002/pcr2.10145 )